2021
DOI: 10.1259/bjr.20210333
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Human Papilloma Virus status on the prediction of head and neck cancer chemoradiotherapy outcomes using the pre-treatment apparent diffusion coefficient

Abstract: Objective: To determine the impact of Human Papilloma Virus (HPV) oropharyngeal cancer (OPC) status on the prediction of head and neck squamous cell cancer (HNSCC) chemoradiotherapy (CRT) outcomes with pre-treatment quantitative diffusion-weighted magnetic resonance imaging (DW-MRI). Methods: Following ethical approval, 65 participants (53 male, age 59.9 ± 7.86) underwent pre-treatment DW-MRI in this prospective cohort observational study. There were 46 HPV OPC and 19 other HNSCC cases with stage III/IV HNSCC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…We found that the ADC and all NG-IVIM parameters were related to HPV status. HPV-negative patients had a higher ADC and NG-IVIM parameter D than HPV-positive patients, which is in line with existing literature [4] , [9] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] . Since HPV-negative patients in general have a worse response to treatment than HPV-positive patients, that finding by itself would suggest that a high ADC is related to a poorer response, which has been reported also before in studies about pre-treatment DWI that did not correct for HPV status [1] , [32] , [33] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that the ADC and all NG-IVIM parameters were related to HPV status. HPV-negative patients had a higher ADC and NG-IVIM parameter D than HPV-positive patients, which is in line with existing literature [4] , [9] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] . Since HPV-negative patients in general have a worse response to treatment than HPV-positive patients, that finding by itself would suggest that a high ADC is related to a poorer response, which has been reported also before in studies about pre-treatment DWI that did not correct for HPV status [1] , [32] , [33] .…”
Section: Discussionsupporting
confidence: 91%
“…Yet, when assessing overall survival, Martens et al [3] did find both pre-treatment high mean ADC and low D* as predictive factors for poor overall survival, while Ravanelli et al [2] did not find any correlation between pre-treatment ADC and overall survival when analyzing the HPV-positive and negative group separately. Similarly, Connor et al [30] did not find a correlation between pre-treatment ADC and disease free survival after 2 years in the subgroup containing HPV-positive OPSCC only, nor in the subgroup of the other head and neck carcinomas (including HPV-negative OPSCC). Therefore, further research is needed to determine the prognostic value of DWI parameters within HPV subgroups.…”
Section: Discussionmentioning
confidence: 89%
“…Magnetic resonance diffusion weighted imaging is an imaging method using the special sequence of magnetic resonance to observe the microscopic diffusion motion of water molecules in living tissue, which is the only imaging technology that can detect the free diffusion activity of water molecules in the absence of invasive operation in humans. It has been used for the diagnosis and treatment of a variety of solid tumors (13)(14)(15). The apparent diffusion coefficient is used to assess the free diffusion activity of water molecules, especially the movement of water molecules in tissue cells.…”
Section: Discussionmentioning
confidence: 99%
“… 94–99 It is proposed that this relates to histological findings of higher stromal content, lower cellularity and micronecrosis, all of which are known to result in greater treatment resistance. 65 Such studies also demonstrated an association between lower pre-treatment ADC values and favourable post-treatment survival outcomes in OPC and other HNSCC; however, until recently, little data were provided on HPV status. 94,96,98,99 It has since been demonstrated that the association between low pre-treatment ADC values and improved outcomes is largely lost when the confounding factor of HPV+ OPC (characterised by lower ADC values) is corrected for.…”
Section: Pre-treatment Structural Imaging With Ct and Mrimentioning
confidence: 99%